Buffers or Boosters? The Role of HRM Practices in Older Workers' Experience of Stereotype Threat. Issue 1 (2nd January 2018) - Oliveira, Eduardo André da Silva; Cabral-Cardoso, Carlos José
ABSTRACT: Building on the social identity approach and the HRM literature, this two-wave cross-sectional study examined the effects of negative age-based metastereotypes on the age-based stereotype threat experience of older workers and on organizational disidentification. The moderator role of HRM practices in the relationship between negative age-based metastereotypes and age-based stereotype threat was also investigated. Older workers survey results ( n = 469) from 14 manufacturing companies indicated that negative age-based metastereotypes correlate positively with stereotype threat. Moderation results showed that age-awareness HRM practices (training for older workers) reinforced age-based stereotype threat, whereas general HRM practices (recognition and respect) impaired it. The article suggests that the combination of age-based metastereotypes with a stereotype threat framework contributes to further understand older workers' beliefs and attitudes. It also indicates that to be effective, HRM practices should emphasize positive social identities older workers share with their colleagues, rather than giving older workers special treatment that may, after all, reinforce stigmatization.